Meta Analisis: Pengaruh Pemberian Vitamin A terhadap Kejadian Stunting pada Anak Usia 6-59 Bulan - Alifariani, Aulia (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
This study aimed to examine the effect of vitamin A on the incidence of stunting in children aged 6-59 months using a meta-analysis. The meta-analysis was carried out using the PRISMA flowchart and the PICO model. Population: children aged 6-59 months. Intervention: giving vitamin A. Comparison: not giving vitamin A. Outcome: stunting. The online databases used are Google Scholar, ProQuest and Elsevier with the keywords “Stunting” AND “Vitamin A” AND “Children Aged 6–59 Months” AND “Multivariate” AND “Cross Sectional”. There were 8 cross-sectional studies published in 2013-2023 that met the inclusion criteria. Analysis was performed with RevMan 5.3. The results of the meta-analysis showed that there was an effect of Children who were not given vitamin A had a risk of being stunted 1.19 times compared to children who were given vitamin A (aOR= 1.19; 95% CI= 1.00 to 1.41; p= 0.050). Conclusion: Children who are given vitamin A reduce the risk of stunting in children aged 6-59 months.